2007
DOI: 10.1080/00071660701463221
|View full text |Cite
|
Sign up to set email alerts
|

The effect of herbs and their associated essential oils on performance, dietary digestibility and gut microflora in chickens from 7 to 28 days of age

Abstract: 1. The effect of the dietary inclusion of 5 culinary herbs or their essential oils on the growth, digestibility and intestinal microflora status in female broiler chicks was assessed. From 7 to 28 d of age, either a basal control diet without supplement was given or one of 10 others, consisting of the basal diet with either 10 g/kg herb (thyme, oregano, marjoram, rosemary or yarrow) or 1 g/kg of essential oil. 2. Body mass (BM) and feed consumption (AFC) were measured on a weekly basis and used to calculate ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
294
8
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(341 citation statements)
references
References 46 publications
30
294
8
9
Order By: Relevance
“…Cross et al (2007) also observed no differences in DMMC and GEMC when assessing the metabolizability influence of different plant extracts. However, the mixture of active principles in the PA of the present study may have shown increased enzyme activity, which promoted improved nutrient metabolizability.…”
Section: Resultsmentioning
confidence: 93%
“…Cross et al (2007) also observed no differences in DMMC and GEMC when assessing the metabolizability influence of different plant extracts. However, the mixture of active principles in the PA of the present study may have shown increased enzyme activity, which promoted improved nutrient metabolizability.…”
Section: Resultsmentioning
confidence: 93%
“…There are many papers, which focused on different feed additives for poultry as an alternative for antibiotic growth promoters (Cross et al, 2007;Gálik et al, 2013 Arpášová et al (2010). Authors reported that major effect of a phytogenic additive in hens nutrition is an decrease of crude fat in egg´s yolk.…”
Section: Resultsmentioning
confidence: 99%
“…There are many papers, which focused on different feed additives for poultry as an alternative for antibiotic growth promoters (Cross et al, 2007;Gálik et al, 2013). Plant extracts, or their ethereal oils are typical for many desirable effects, such as inhibition of pathogen microorganism and stimulation of same desirable physiological processes (Gali-Muhtasib et al, 2006;Yazan et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…For example some studies indicated a lack of a positive effect of thymol in the cornsoybean meal based diets (Lee et al, 2003b;Jang et al, 2004;Sengul et al, 2008;Rahimi et al, 2011) on growth performance. In contrast, other authors have reported the beneficial effect of thymol on broiler growth performance (Bassett, 2000;Hertrampf, 2001;Kamel, 2001;Bolukbasi et al, 2006;Cross et al, 2007;Bolukbasi and Erhan, 2007).…”
Section: Introductionmentioning
confidence: 90%